Os desafios do acesso à justiça ao sujeito migrante: a questão do reconhecimento - Ronsini, Marina Mayora (2024)
Based on the understanding that in the individual-society relationship, there is a rationality present in the structure of the nation-state that cuts across the most diverse intersubjective dimensions of the immigrant subject, this study will be based on the three categories present in Axel Honneth's theory of recognition - the sphere of love, law and solidarity. These categories support the research problem that guides this work, which is formulated as follows: how does the exclusion of immigrants affect their lack of access to justice? Through the theoretical elaboration of the first category, the aim is to evaluate the impact of recognition, especially denied recognition, on immigrants, when situated in the sphere of love. Through the second category, we intend to make a qualitative assessment of the cognitive respect enjoyed by the immigrant individual through legal recognition. Similarly, through the theoretical elaboration in the third category, we intend to carry out a qualitative diagnosis of the social esteem enjoyed by immigrants. The empirical basis of the study is supported by the field diaries produced from the experience of providing legal and documentary advice in an extension context. At first, we problematize how the imaginary of the nation is constructed and reflected in social structures, mainly through the eyes of social psychology, articulated with the legal field, understanding that this is one of the ways to better work on the sources of recognition for immigrant subjects. In the second part of the paper, we focus on the contribution of Honneth's recognition thesis to the fact of immigrant exclusion, and then analyze (in)access to justice based on field diaries.